Theoretical and conceptual analysis: Aflatoxin intervention of Mindanao, Philippines - R. E. G. A. Cataluña; R. L. Base (Пищевые системы, 2025)
This study examines the Aflatoxin Intervention Program being implemented by the Department of Agriculture Regional Field Office 10 in Bukidnon, Northern Mindanao, Philippines, through the lenses of the Health Belief Model (HBM) and Social Cognitive Theory (SCT). Using a descriptive, correlational, survey design, the data from 34 corn farmers across six municipalities were analyzed. The design analyzes their awareness of aflatoxin toxicity, adoption of mitigation protocols and access to media platforms. Findings show high awareness and adoption of aflatoxin mitigation protocols, but a significant part of the participants remains unaware, thus indicating growth points for improvement. High awareness of the mitigation protocols suggest that communication strategies have been effective and observational learning is critical in the awareness process. High adoption rates among early and mainstream adopters of the mitigation protocols convey practical impact of the awareness and educational programs of the department. Media platform access shows weak impact, highlighting the need for more interactive educational strategies. Strong correlations between awareness and adoption rates validate HBM and SCT principles, emphasizing perceived severity, benefits, and self-efficacy. Insights into effective communication strategies underline the importance of targeted, community-based interventions that promote adoption of aflatoxin mitigation protocols. These findings contribute to food safety and wider adoption of good agricultural practices in corn cultivation, providing a framework for future studies and interventions to enhance aflatoxin management in Northern Mindanao.